Distributed Cooperative Transmission with Unreliable and Untrustworthy Relay Channels - Zhu Han; Yan Lindsay Sun (EURASIP Journal on Wireless Communications and Networking, 2009)
Cooperative transmission is an emerging wireless communication technique that improves wireless channel capacity through multiuser cooperation in the physical layer. It is expected to have a profound impact on network performance and design. However, cooperative transmission can be vulnerable to selfish behaviors and malicious attacks, especially in its current design. In this paper, we investigate two fundamental questions Does cooperative transmission provide new opportunities to malicious parties to undermine the network performance? Are there new ways to defend wireless networks through physical layer cooperation? Particularly, we study the security vulnerabilities of the traditional cooperative transmission schemes and show the performance degradation resulting from the misbehaviors of relay nodes. Then, we design a trust-assisted cooperative scheme that can detect attacks and has self-healing capability. The proposed scheme performs much better than the traditional schemes when there are malicious/selfish nodes or severe channel estimation errors. Finally, we investigate the advantage of cooperative transmission in terms of defending against jamming attacks. A reduction in link outage probability is achieved.